The Influence of Dynamic Capabilities on Business Performance with Innovation as a Mediating Variable - Melanie, Gandhisa Septry (Universitas Airlangga, 2026)
This explanatory quantitative study aims to analyze the influence of dynamic capabilities on business performance in culinary MSMEs in Malang City, with innovation as a mediating variable. The study involved 120 decision-makers from those enterprises, selected using a non-probability sampling method with purposive sampling technique. The data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. This study finds that dynamic capabilities significantly affect innovation, dynamic capabilities have a direct effect on business performance, innovation significantly affects business performance, and innovation partially mediates the relationship between dynamic capabilities and business performance. These findings highlight the importance for culinary MSME actors to strengthen their adaptive, absorptive, and innovative capabilities to drive the development of superior products and processes, thereby enhancing competitiveness and business sustainability.